2012
DOI: 10.2478/v10283-012-0018-2
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Variations of the Incidence of Ruptured Abdominal Aortic Aneurysm at the Territory of the South Serbia

Abstract: Literature data on the association between the incidence of ruptured abdominal aorta and seasons are contradictory. The influence of climatic factors on the rupture of abdominal aorta is geographically dependent.The aim of this research was the investigation of the connection between the incidence of ruptured abdominal aorta and seasons at the territory of the southern Serbia.In this retrospective study, 59 consecutive patients, who were hospitalized in the Vascular Surgery Clinic, Clinical Center Niš, between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
1
2
0
Order By: Relevance
“…Most studies report a seasonal variation of rAAA, with autumn and winter (mostly autumn) being the seasons with the highest incidence of rupture. 711,13,16,17,2026 Our results are in line with these findings. Climatic conditions such as low mean atmospheric pressure, 3,9,1012 4-day variances in atmospheric pressure as independent factors, 8 low temperatures, 8,27,28 high atmospheric pressure, 29 low humidity, 29 and low global solar irradiation 30,31 have been related to rAAA occurrences.…”
Section: Discussionsupporting
confidence: 92%
“…Most studies report a seasonal variation of rAAA, with autumn and winter (mostly autumn) being the seasons with the highest incidence of rupture. 711,13,16,17,2026 Our results are in line with these findings. Climatic conditions such as low mean atmospheric pressure, 3,9,1012 4-day variances in atmospheric pressure as independent factors, 8 low temperatures, 8,27,28 high atmospheric pressure, 29 low humidity, 29 and low global solar irradiation 30,31 have been related to rAAA occurrences.…”
Section: Discussionsupporting
confidence: 92%
“…There were 17 studies 10,12,14,17,19,[21][22][23][25][26][27]29,32,35,37,39,41 (n ¼ 17,26,335; Figs 3-5), all of which were from the Northern Hemisphere, that analyzed the seasonal variations of rAAA. The pooled proportion of rAAA was highest in the autumn season (incidence rate, 26.6%; 95% CI, 25.6%-27.7%; I 2 ¼ 15.4%), followed by winter (incidence rate, 26.2%; 95% CI, 24.1%-28.2%; I 2 ¼ 72.4%), spring (incidence rate, 24.4%; 95% CI 23.0%-25.9%; I 2 ¼ 41.9%), and summer (incidence rate, 21.1%; 95% CI, 19.3%-23.0%; I 2 ¼ 70.4%).…”
Section: Seasonal Variation Of Raaamentioning
confidence: 99%
“…A quality assessment of included studies was performed using an author-modified Newcastle-Ottawa Scale with a mean score of 6/9. Eight studies scored 4 points and below 14,17,18,24,29,30,33,38 and were deemed to be methodologically weak. We identified a few consistent weaknesses among the included studies.…”
Section: Journal Of Vascular Surgerymentioning
confidence: 99%
“…8 The relative hypercoagulability observed during colder weather further increases the risk of DVT, as seasonal variation elevates fibrinogen levels, leading to hypercoagulability. 4,6,[9][10][11] It is suggested that cold weather may induce vasoconstriction, resulting in reduced blood flow in the veins of the lower limbs due to decreased physical activity, while respiratory tract infections during winter may also lead to fluctuations in coagulation, contributing to the seasonal variation. Additionally, it has been hypothesized that temperature fluctuations and chilling may influence cardiovascular mortality.…”
Section: Discussionmentioning
confidence: 99%